An Arabic Sedentary Behaviors Questionnaire (ASBQ): Development, Content Validation, and Pre-Testing Findings - Hazzaa M. Al-Hazzaa; Shaima A. Alothman; Nada M. Albawardi; Abdullah F. Alghannam; Alaa A. Almasud (Behavioral Sciences, 2022)
Background: Sedentary behaviors (SB) are very prevalent nowadays. Prolonged sitting associates with chronic disease risks and increased mortality even while controlling for physical activity. Objective measurement of SB is costly, requires technical expertise, and is challenging in terms of time and management. Currently, there is no validated self-reported instrument in the Arabic language that assesses SB among individuals and relates sedentary time to social, environmental, and health outcomes. The aim of this research was to develop a multi-item Arabic SB questionnaire (ASBQ). Methods: The ASBQ was developed through an extensive literature review and discussion by the research team (n = 5), then went through content validation (n = 10 experts) and pre-testing using cognitive interviewing procedures (n = 51 respondents, mean (SD) age was 38.3 (18.2) years, and with 49% females). Results: The ASBQ included 13 questions comprising a wide range of sedentary activities. The Arabic SB instrument showed excellent content validity for assessing sedentary time in adolescents and adults with a very high item-level and scale-level content validity index. A kappa statistic, a measure of interrater reliability, was 0.95. The pre-testing showed that the instrument was highly rated by a diverse sample of Saudi adolescents and adults. Conclusion: The ASBQ received excellent acceptance by a panel of experts with promising pre-test results. Further testing of psychometric properties, including test-retest reliability and criterion validity is required.